Design of Wideband Antenna for RF Energy Harvesting System - Zainuddin, N. A; Zakaria, Z; Husain , M. N; Mohd Derus, B; Abd Aziz, M. Z. A; Mutalib, M. A; Othman, M. A (2013)
This paper studies a wideband antenna of ice-cream cone structure and it is integrated with a rectifying circuit which has the potential to be used for RF energy harvesting system. The antenna is designed by using CST Studio Suite 2011 and fabricated on a double sided FR-4 printed circuit board using an etching technique. A single stage rectifying circuit is designed, simulated, fabricated and measured in this work. The design and simulation process was done by using Agilent Advanced Design System (ADS) 2011. Simulation and measurement were carried out for various input power levels at the specified frequency band. An experimental test has been conducted by varying the load, R of the rectifying circuit. For an equivalent incident signal of 20 dB, the system managed to produce 0.09V with load of 20k'. This voltage can be used to power low power sensors in sensor networks ultimately in place of batteries.